Contextual Learning Based on Visual-Spatial Intelligence to Improve Beginner-Level Understanding of Mufradat Arabic - Muhammad Afthon Ulin Nuha; Machrup Eko Cahyono; Nurul Zuhriyah; Mas Tajuddin Ahmad; Nurul Musyafaah (Insitut Muslim Cendekia, 2025)
By utilizing visual media such as videos and picture cards, this method aims to enhance students' understanding of Arabic vocabulary. This study was conducted at As-Salma Bahrul Ulum Tambakberas Jombang, involving class A as the control group and class B as the experimental group. Using a quantitative approach and quasi-experimental design, the instruments employed were multiple-choice test, and data analysis was performed using the t-test. The results demonstrate that contextual learning based on visual-spatial intelligence successfully aids students understanding arabic vocabulary. Class B achieved a perfect score of 28.57%, while the control class had no students reached a perfect score. Additionally, 14.29% of students in class B required further guidance, whereas 38.1% of students in the control class needed assistance. The t-test results showed a t-value of 3.40 with a p-value of 0.0008, which is lower than the significance level. This indicates that contextual learning based on visual-spatial intelligence is effective to improved the understanding of Arabic vocabulary among beginner students.